The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.12944/crnfsj.6.2.28
|View full text |Cite
|
Sign up to set email alerts
|

Study of the National Cooked Smoked Meat Products While Tests with Laboratory Animals at the Pathology Models with the Purpose to Confirm the set of Biocorrective Features

Abstract: Conducted physico-chemical and biological studies of Goji berries and national products made it possible to obtain information on the bioavailability of nutrients included in the product, to evaluate their food value and nutritional value, and their functional orientation. The study of the processes of digestibility and absorption of the developed products on the gastric invitro model and the monolayer of the intestinal wall epithelium showed high absorption and assimilability of the low molecular weight (from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Previous studies revealed that meat trimmings from heads of cattle have lower vitamin and microelement contents compared to beef (Berdutina, 2000;Bondarenko and Elizarova, 2014;Makangali et al, 2018;Verma et al, 2008). At the same time, it has a sufficient level of protein content with a higher total content of essential amino acids in comparison with beef -the content of essential amino acids in beef is 37.07 g.100g -1 of protein, and in the head of cattle -38.66 g.100g -1 of protein.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that meat trimmings from heads of cattle have lower vitamin and microelement contents compared to beef (Berdutina, 2000;Bondarenko and Elizarova, 2014;Makangali et al, 2018;Verma et al, 2008). At the same time, it has a sufficient level of protein content with a higher total content of essential amino acids in comparison with beef -the content of essential amino acids in beef is 37.07 g.100g -1 of protein, and in the head of cattle -38.66 g.100g -1 of protein.…”
Section: Resultsmentioning
confidence: 99%
“…An effective way to solve this problem is to develop cooked sausages using functional ingredients based on a combination of meat and vegetable raw materials. Meat products, in particular, cooked sausage products, can be considered as a basic basis for creating products that have functional and technological properties that provide the human body with not only full-fledged protein, but also vitamins, minerals and dietary fibers through the use of bioactive agricultural plant raw materials (Karapetyan, 2015;Makangali et al, 2018;Ivanova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It preserves and improves health and reduces the risk of developing nutrition-related diseases. Enriched foods include functional foods obtained by adding physiologically functional ingredients to traditional foods to prevent or correct a nutrient deficiency in the human body [7,8].…”
Section: Introductionmentioning
confidence: 99%